Analysis On Installation, Testing And Commissioning Of Automatic Platform Gate (APG) And Platform Screen Door (PSD)” - Hasnan, Muhammad Aziq Firdaus (Progress in Engineering Application and Technology, 2022)
Railway transit is one of the most common modes of public transportation for people nowadays. Therefore, when developing public rail transit, one of the most critical considerations is safety. Automatic Platform Gate (APG) and Platform Screen Door (PSD) is one of the precautionary measures that has been implement by railway services in railway station to improve the safety. It is a system that separates the platform from the train track to prevent the passenger from accidently fall into the track. However, the issue that arises here is that failure of components happened during installation and testing procedure. Hence, the objective of this project is to investigate the failure and root causes during installation and testing procedure of APG/PSD. The design of APG/PSD system is discussed in the literature review chapter of this project. While doing the testing procedure the faulty components will be recorded. Result of investigation shows that the limit switch is one of the failures that always happened. Therefore, a new model of limit switch will be used to replace the previous one. Before the new model can be implement at stations, it needs to be tested first. Only after it pass the requirement needed, the new model can be used at stations